Efek Relaksasi Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi - Moh Alimansur; Mohamad Choirul Anwar (Akademi Keperawatan Dharma Husada Kediri, 2013)
Relaxation techniques are increasingly being done because it proved effective in reducing tension and anxiety. Purpose this study was to determine the effect of relaxation techniques to decrease blood pressure in hypertensive patients. The design of this study is the Pre Experimental Designs with a kind of One Group Pretest-posttest Designs. Populations of all citizens of hypertension in August 2011 obtained 21 respondents using Simple Random Sampling, sample a total of 11 respondents. Independent research variables in this study are relaxation techniques and the dependent variable is a decrease in blood pressure in hypertensive patients. The collection of data using counseling and observation. Using interval scale data processing through editing, coding, tabulating and scoring. Analyze data using the Wilcoxon match pairs - test. The results of the 11 respondents found 9 respondents (82%) experienced a decrease in blood pressure and second respondents (18%) did not decrease blood pressure. From the research we can conclude there is the influence of relaxation techniques to decrease blood pressure in hypertensive patients. It is influenced by the age of respondents and the respondents' psychological condition. It is hoped the community can continue to apply in families with hypertension, one of the methods of blood pressure reduction through non-pharmacological methods to perform breathing relaxation techniques in addition to pharmacological therapy. Key words: influence, relaxation, decreased blood pressure